Progress in research on gut microbiota in ethnic minorities in China and consideration of intervention strategies based on ethnic medicine: A review - Chen, Rong; Duan, Zhong-Yu; Duan, Xiao-Hua; Chen, Qing-Hua; Zheng, Jin (Frontiers in Cellular and Infection Microbiology, 2022)
One of the variables affecting gut microbiota is ethnicity. There are 56 ethnic subgroups in China, and their intestinal flora differs. A wealth of medical resources has also been produced by the presence of numerous ethnic minorities. In this study, we reviewed the pertinent literature on the intestinal flora of ethnic minorities in China and abroad using the CiteSpace visualization software, and we used bibliometric techniques to find the most widely prescribed medications for preventing and treating endemic diseases in ethnic minorities. Based on the gut microbiology of minority populations, we suggest that by comprehensive development involving literature, experimental, and clinical research, the pharmacological action mechanisms for interventions in endemic diseases can be drawn from ethnic medicine. This point of view has not been discussed before and will offer a fresh perspective on the creation and application of ethnic medications as well as a fresh method for the management of prevalent diseases in ethnic communities.